Análisis de la presencia del sector agrícola quinuero en los buscadores locales de Bolivia - Noelia Debbie Magne Andia; María Cecilia Lenis Abastoflor (Institute for Advanced Development Studies (INESAD), 2024)
– Quinoa, a seed esteemed for its nutritional properties and deeply rooted historical significance in the southern highlands of Bolivia for over 6,000 years, has witnessed a transformation in its current landscape. Despite having been the world's primary producer of this grain in the past, Bolivia has relinquished its leadership, grappling with challenges related to performance and competitiveness when compared to other nations. This paper advocates for the implementation of marketing strategies, specifically focusing on Search Engine Marketing, to enhance the online visibility of Bolivian quinoa and thereby rejuvenate its presence in the global market. To achieve this objective, an analysis of the online presence of this product is conducted, accompanied by recommendations for its improvement.
Keywords: M30; M31; M37; 330; Digital Marketing; online presence; web analytics; search engine strategies; SEO; SEM